2004
DOI: 10.1128/jvi.78.14.7565-7574.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Obstacles to Human Immunodeficiency Virus Type 1 Coreceptor Switching

Abstract: The natural evolution of human immunodeficiency virus type 1 infection often includes a switch in coreceptor preference late in infection from CCR5 to CXCR4, a change associated with expanded target cell range and worsened clinical prognosis. Why coreceptor switching takes so long is puzzling, since it requires as few as one to two mutations. Here we report three obstacles that impede the CCR5-to-CXCR4 switch. Coreceptor switch variants were selected by target cell replacement in vitro. Most switch variants sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(137 citation statements)
references
References 54 publications
9
127
0
1
Order By: Relevance
“…2, lane 5). N-terminal sequencing of both ϳ120 kDa bands resulted in the sequence EKLWVTVYYGVPVWK, which corresponds with 100% accuracy to the known N-terminal sequence of gp120 BaL (22).…”
Section: Sp-a Targets the Gp120 Envelope Protein Of Hivmentioning
confidence: 99%
“…2, lane 5). N-terminal sequencing of both ϳ120 kDa bands resulted in the sequence EKLWVTVYYGVPVWK, which corresponds with 100% accuracy to the known N-terminal sequence of gp120 BaL (22).…”
Section: Sp-a Targets the Gp120 Envelope Protein Of Hivmentioning
confidence: 99%
“…V3 determines which coreceptor is used by the virus (Hwang et al 1991) through its sequence variation (Dittmar et al 1997;Speck et al 1997;Cormier and Dragic 2002), although have shown that the contiguous first and second variable regions (V1/V2) and the second conserved region (C2), which separates V1/V2 from V3, may also be involved. Pastore et al (2004) used selection experiments to identify the amino acid changes putatively involved in coreceptor switching. They selected for CXCR4 use in CCR5-adapted HIV-1 strains by passaging (serially transferring) virus through cell cultures containing progressively increasing proportions of CXCR4-expressing cells.…”
mentioning
confidence: 99%
“…It is generally believed that relatively late appearance of X4 virus variants is driven by evolution of virus population during the course of disease [42]. This assumption is in conflict with viral property of rapid turnover of about 10 10 to 10 12 virions every two days combined with the high mutation rate of HIV [42][43][44][45][46][47][48][49][50]. This should result in emergence of X4 variants fairly early during infection, especially because, in some cases, only two mutations are thought to be necessary for co-receptor switch.…”
Section: Cd25mentioning
confidence: 99%